Implementasi Pembelajaran Berdiferensiasi dengan Memanfaatkan Media Lose Part untuk Mewujudkan Profil Belajar Pancasila di TK Aceh Besar - Inayah, Inayah; Mardhatillah, Mardhatillah; Mudsiani, Mudsiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the implementation of differentiated learning using loose part media in realizing the pancasila profile can be implemented in Aceh Besar Regency. The method used in this study uses qualitative methods or approaches with descriptive methods as a series of activities related to reading, observing, recording, and documenting and processing research materials. The subjects of this study were carried out in 2 schools, namely TK Negeri Pembina Baet Sukamakmur and TK Negeri Pembina 2 Kuta Malaka. Data analysis is carried out qualitatively with stages of data reduction, data presentation, and conclusion drawing. The results of this study show that implementing differentiated learning using loose part media in realizing the Pancasila student profile is one of the policies that can realize national education and is a role in strengthening the character of children from an early age which will continue to become self-competence in the school environment and community in accordance with the 6 dimensions in the Pancasila student profile who are able to face the challenges of the current era. Of course, by using loose part media through differentiated learning, children can carry out various activities that suit their talents and interests